SUNNY WAYS OR SOMBER WEATHER? INTERNATIONAL MANAGEMENT CONSULTANTS AND APPRAISAL OF POLICY CAPACITY - Hunter, Darryl (PEOPLE: International Journal of Social Sciences, 2017)
Nearly three hundred judgments of policy capacity within one of three Ministries of Education in a South Pacific country are closely scrutinized for their accuracy. A clearly discernable and measurable halo, or its horned converse, a less positive interpretation, was apparent when internal and external raters used a modified United Nations Development Programme scale during interviews. The scale was augmented with criteria recognizing some desirable traits for civil servants. Those criteria centered on recognizing the warranting nature of various types of evidence, professional knowledge of education policy/processes, and persuasive ability of the person. North American research in cognitive science, organizational behaviour, social psychology and pragmatic-legal theories of evidence offer four explanations. The latter two theories appear to best explain overly positive or negative views of an organization’s capacity. Implications are drawn for management consultants and researchers alike when working on international development projects.